Direct conversion of biomass-derived carbohydrates to 5-hydroxymethylfurural over water-tolerant niobium-based catalysts. (1st January 2015) - Zhang, Yu; Wang, Jianjian; Li, Xiangcheng; Liu, Xiaohui; Xia, Yinjiang; Hu, Bicheng; Lu, Guanzhong; Wang, Yanqin
Graphical abstract: Highlights: One-pot conversion of glucose to HMF in aq. solution can be realized with high yield. Mesoporous NbOPO4 with tunable acidity and L/B acid ratio was synthesized. Lewis acid played a key role in the isomerization of glucose to fructose. More Lewis acid would lead to the formation of humins in the next dehydration step. The balance between L/B acid types is important for the conversion of glucose to HMF. Abstract: A series of water-tolerant porous niobium phosphate solid acid catalysts were hydrothermal synthesized using cetyltrimethyl ammonium bromide (CTAB) as the template. The tuning of surface acidity and the ratios of acid types (Brönsted and Lewis acid sites) was realized by adjusting the pH values in synthetic processes. It was found that the acidic properties and the balance between Brönsted/Lewis acid types of solid acid catalysts had great influence on the selective conversion of glucose or glucose-united carbohydrates, such as sucrose, cellobiose, starch and cellulose into 5-hydroxymethylfurural (HMF) in pure water. It is found that Lewis acid sites played an important role in the isomerization of glucose into fructose, whereas excessive Brönsted acid sites had detrimental effect on this isomerization process; Brönsted acid sites were active for further dehydration of generated fructose to HMF, but excessive Lewis acid would lead to the formations of by-products (e.g., humins) and decrease the selectivity to HMF. Under optimal reaction conditions, as high as 33.2% yield of HMF can be obtained from glucose in pure water over porous niobium phosphate catalyst synthesized at pH = 7. The yield of HMF can be slightly increased to 39.3% in a biphasic water/methyl isobutyl ketone medium. Furthermore, this catalyst also displayed excellent performances on the conversion of other carbohydrates and exhibited high recycle stabilities.